2000
DOI: 10.1093/ajcn/71.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effectiveness of mandatory iodization of table salt, at an elevated iodine concentration, on the iodine and goiter status of schoolchildren with endemic goiter

Abstract: Mandatory iodization of salt virtually eradicated iodine deficiency within 1 y in South African schoolchildren, but the goiter rate in these children did not decline. Measurement of goiters by palpation may not be appropriate in short-term evaluations of mandatory iodization programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 13 publications
(13 reference statements)
1
41
1
2
Order By: Relevance
“…37 As a consequence a dramatic shift occurred, also within one year, in the distribution of urinary iodine values from deficient to sufficient concentrations in four communities in the Langkloof area. 12 The goitre rates in these children, measured by palpation, remained unchanged after a year, confirming the slow regression of the thyroid size after increasing the iodine intake observed in the Ivory Coast. 3 This data also indicated that goitres measured by palpation may not be appropriate in the short-term evaluation of changes in salt iodisation programmes.…”
Section: Impact Of Mandatory Iodisation Of Saltsupporting
confidence: 59%
See 1 more Smart Citation
“…37 As a consequence a dramatic shift occurred, also within one year, in the distribution of urinary iodine values from deficient to sufficient concentrations in four communities in the Langkloof area. 12 The goitre rates in these children, measured by palpation, remained unchanged after a year, confirming the slow regression of the thyroid size after increasing the iodine intake observed in the Ivory Coast. 3 This data also indicated that goitres measured by palpation may not be appropriate in the short-term evaluation of changes in salt iodisation programmes.…”
Section: Impact Of Mandatory Iodisation Of Saltsupporting
confidence: 59%
“…The cut-off levels and interpretation of iodine status are provided in Table II. 2 The thyroid size of children aged 6 to 12 years has been used as biological marker of iodine deficiency for many years, but its usefulness is limited because the thyroid size regresses slowly after increasing the iodine intake in salt iodisation programmes, 12,13 and results need to be interpreted cautiously. Thyroid size determined by palpation is graded as Grade 0 when the thyroid is not palpable, Grade 1 when it is palpable but not visible and the size of the lobe is bigger than the size of the end digit of the thumb of the Overall, iodine deficiency produces subtle but widespread adverse effects in a population, including decreased educability, apathy, and reduced work productivity, resulting in impaired social and economic development.…”
Section: Assessment Of Iodine Statusmentioning
confidence: 99%
“…Legislations to controls the tobacco exposure [93] and fortification of salt with iodine [94] are some examples of this approach.…”
Section: Population Approachmentioning
confidence: 99%
“…There is therefore no further need to add iodine to a fortified biscuit distributed in South African schools. The effectiveness of the mandatory salt iodisation programme in South Africa was evaluated by Jooste et al 20 and shown to be effective in virtually eradicating iodine deficiency, as measured by urinary iodine excretion, in a group of school children within one year.…”
mentioning
confidence: 99%